2022
DOI: 10.1007/s42380-022-00137-7
|View full text |Cite
|
Sign up to set email alerts
|

Participant Role Behavior in Cyberbullying: an Examination of Moral Disengagement Among College Students

Abstract: The current study examined the role of moral disengagement in cyberbullying participant role behavior among college-aged individuals. Participants included 434 students who completed surveys measuring their participation in cyberbullying, including online bystander role behaviors, as well as their moral disengagement. Regression analysis results indicated that moral disengagement was positively associated with cyberbullying perpetration, cyberbullying victimization, passive bystanding online behavior, and rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…However, with the addition of the situational characteristics, perceived popularity and the psychosocial cost of defending, higher levels of moral disengagement were found to be significantly related to passive outsider behaviour online, contradicting our hypothesis. This finding is consistent with the literature suggesting that high levels of moral disengagement is associated with passive defending online (Jeong et al, 2022;Nagar et al, 2022), whereas other studies have indicated that low levels of moral disengagement were related to passive bystanding online (Lo Cricchio et al, 2020;Sarmiento et al, 2019). At the same time, research has also revealed that moral disengagement was not associated with passive bystanding online (Lo Cricchio et al, 2020;Sarmiento et al, 2019), suggesting that the connection between moral disengagement and passive outsiders online is uncertain.…”
Section: Individual Characteristicssupporting
confidence: 93%
“…However, with the addition of the situational characteristics, perceived popularity and the psychosocial cost of defending, higher levels of moral disengagement were found to be significantly related to passive outsider behaviour online, contradicting our hypothesis. This finding is consistent with the literature suggesting that high levels of moral disengagement is associated with passive defending online (Jeong et al, 2022;Nagar et al, 2022), whereas other studies have indicated that low levels of moral disengagement were related to passive bystanding online (Lo Cricchio et al, 2020;Sarmiento et al, 2019). At the same time, research has also revealed that moral disengagement was not associated with passive bystanding online (Lo Cricchio et al, 2020;Sarmiento et al, 2019), suggesting that the connection between moral disengagement and passive outsiders online is uncertain.…”
Section: Individual Characteristicssupporting
confidence: 93%
“…Moreover, the gamified tasks allowed participants, to experience the consequences of being prosocial, since they receive a message from the victim, thanking them for their support. Thus, by receiving this type of social reward, the cognitive costs of feeling empathy, might decrease [ 49 ], which could lead to higher feelings of empathy, and consequently, lower levels of MD. Finally, we examined how with these gamified tasks, participants may be able get a deeper understanding of how much their support can be important in real life situations, how they can act prosocially, and how they can have a positive impact by setting the example in their peer group.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy is a complex psychological phenomenon of key importance in social interaction [ 48 ], which plays an important role in moral development [ 49 ], including in emotions, attitudes and behavior [ 50 ]. Empathy can be viewed as both as emotional and a cognitive response to other people’s situations and refers to the ability to understand and feel the emotions of others [ 51 ].…”
Section: Bystanders Of Cyberbullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyberbullying, which was briefly mentioned in the introduction, is another field of research which could be explored further in the context of HE. Some studies have already investigated different issues with regards to cyberbullying in HE (Byers & Cerulli, 2021;Doane et al, 2020;Gahagan et al, 2016;Hayashi & Tahmasbi, 2020Huang et al, 2023;Jeong et al, 2022). While there seems to be a trend towards research on cyberbullying at all educational levels, we decided to focus on traditional in-person relational bullying in this study as the research foundation on traditional bullying in HE and the role of bystanders in it is still considered scarce and ought not to be overlooked.…”
Section: Limitationsmentioning
confidence: 99%